THE NARRATIVE CHARACTERISTICS OF ISLAMIC TERRORISM DISCOURSES - Ridwan Rosdiawan (Al-Albab, 2014)
While polemics is still shadowing the internationally accepted definition, the word “Terrorism” becomes more controversial when it is paralleled with “Islam”. The Islamic Terrorism discourse is more likely to be an elusive concept if not a Fata Morgana. Its very existence appears as a real entity but its form can hardly be described. It would be always be problematic to posterize such a terrible notion as “terrorism” and put it side by side with a noble concept as in “Islam”. The fact, however, shows that the two-word has been widely discussed in global arena. “Islamic Terrorism” has become a trending topic in global politics and academic discourses in the first decade of the millennium.